Probiotics in the prevention and management of human diseases : a scientific perspective - Dwivedi, Mitesh Kumar; Amaresan, N.; Sankaranaryanan, A.; Kemp, Helen (Academic Press, 2022)
Probiotics in The Prevention and Management of Human Diseases: A Scientific Perspective addresses the use of probiotics and their mechanistic aspects in diverse human diseases. In particular, the mechanistic aspects of how these probiotics are involved in mitigating disease symptoms (novel approaches and immune-mechanisms induced by Probiotics), clinical trials of certain probiotics, and animal model studies will be presented through this book. In addition, the book covers the role of probiotics in prevention and management aspects of crucial human diseases, including multidrug resistant infections, hospital acquired infections, allergic conditions, autoimmune diseases, metabolic disorders, gastrointestinal diseases, neurological disorders, and cancers. Finally, the book addresses the use of probiotics as vaccine adjuvants and as a solution for nutritional health problems and describes the challenges of using probiotics in management of human disease conditions as well as their biosafety concerns. Intended for nutrition researchers, microbiologists, physiologists, and researchers in related disciplines as well as students studying these topics require a resource that addresses the specific role of probiotics in the prevention and management of human disease.